Increased Tear Film Osmolarity in Systemic Lupus Erythematosus. (3rd September 2017) - Duru, Necati; Altinkaynak, Hasan; Uysal, Betul Seher; Duru, Zeynep; Can, Mehmet Erol; Erten, Sukran; Yuksel, Nilay; Kalkan Akcay, Emine
Abstract: Purpose : To evaluate tear film osmolarity in patients with systemic lupus erythematosus (SLE). Methods : A total of 55 eyes from 55 patients with SLE and 47 eyes from 47 age- and gender-matched healthy individuals were included in this study. Tear film osmolarity was evaluated with a lab-on-a-chip technique (TearLab; TearLab Corporation, San Diego, CA) in SLE patients in comparison with healthy individuals, and results were correlated to clinically available diagnostic tests for dry eye, such as tear ﬁlm break-up time (BUT), Schirmer's test, and Ocular Surface Disease Index (OSDI). Results : The mean tear film osmolarity in the SLE patients and healthy individuals was 306.02 ± 13.27 mOsm/L and 300.74 ± 9.11 mOsm/L, respectively, which made for a statistically significant difference ( p = 0.020). In the SLE group, tear film osmolarity was negatively correlated with the Schirmer's test score and the BUT value ( r = −0.295 p = 0.029 and r = 0.347 p = 0.009, respectively), whereas tear film osmolarity was not correlated with OSDI score ( r = −0.182 p = 0.183). Conclusions : This study revealed that tear film hyperosmolarity and abnormal tear film function are associated with SLE.